Current status and development of membranes for CO2/CH4 separation: A review - Zhang, Y.; Sunarso, J.; Liu, Shaomin; Wang, R. (Elsevier, 2013)
Carbon dioxide (CO2) is a greenhouse gas found primarily as a main combustion product of fossil fuel as well as a component in natural gas, biogas and landfill gas. The interest to remove CO2 from those gas streams to obtain fuel with enhanced energy content and prevent corrosion problems in the gas transportation system, in addition to CO2 implications to the climate change, has driven the development of CO2 separation process technology. One type of technology which has experienced substantial growth, breakthroughs and advances during past decades is membrane-based technology. The attractive features offered by this technology include high energy efficiency, simplicity in design and construction of membrane modules and environmental compatibility. The objective of this review is to overview the different types of membranes available for use including their working principles, current status and development which form the primary determinants of separation performance and efficiency. The emphasis is toward CO2/CH4 separation, considering its substantial and direct relevance to the gas industry. To this end, discussion is made to cover polymeric gas permeation membranes; CO2-selective facilitated transport membranes, hollow fiber gas–liquid membrane contactors, inorganic membranes and mixed matrix membranes.The market for CO2 separation is currently dominated by polymeric membranes due to their relativelylow manufacturing cost and processing ability into flat sheet and hollow fiber configurations as well aswell-documented research studies. While there have been immensely successful membrane preparation and development techniques with consequential remarkable performance for each type of membrane. Each type of membrane brings associated advantages and drawbacks related to the characteristic transport mechanism for specific application conditions. Inorganic membranes, for example, are very suitable for high temperatureCO2 separation in excess of 400 ?C while all other membranes can be applied at lower temperatures. The recent emergence of mixed matrix membranes has allowed the innovative approach to combine the advantages offered by inorganic and polymeric materials.